Potensi Artificial Intelligence dalam Dunia Kreativitas Desain - Dwina Satrinia; Reza Ramadani Firman; Trimalda Nur Fitriati (PPM Telkom University, 2023)
The shift in cultural practices towards digital usage has led companies and product brands to become increasingly adept at utilizing social media for promotion and branding. Creating social media content requires creativity, interactivity, attractiveness, and speed, driving a growing demand for design skills. To support the design process, designers rely on various tools, including AI-integrated applications, such as Canva, Figma, Picsart, Adobe Photoshop, Adobe Lightroom, and others. These tools enhance graphic designers' productivity and enable them to edit images, create artworks, and produce creative content for social media. The research explores the usage of AI technology in the field of design and art. It examines several AI applications, including image segmentation, image enhancement, image-to-image translation, face attribute manipulation, creating new artistic expressions, detecting fake paintings, 3D art, and AI influencers. AI has positively impacted the creative design world by enabling artists to explore new artistic expressions, generate more personal and interactive artworks, and streamline the design workflow. AI tools have also facilitated inclusive design, making creative content accessible to diverse audiences. However, there are concerns that AI may replace human artists and create art lacking soul or authenticity. The research aims to provide an overview of the existing studies on AI in design to help designers understand the potential of AI in the creative domain. It also discusses the positive and negative implications of AI's integration into the world of design, emphasizing the need for ethical considerations and the preservation of human artistic contributions.